Analysis of Monetary Policy on Inflation in Influencing Economic Growth According to the Perspective of Islamic Economics - Mega Dewi Sri Utami; Nanda Alfreda Putri; Qurrotul Uyun (Penerbit Hellow Pustaka, 2025)
One of the indicators used in the scope of macroeconomics to identify and measure the stability of a country's economy is inflation. From an economic perspective, inflation is an event in which the general price level continues to increase. In cases where inflation continues to occur over a long period of time. Therefore, it can cause unrest in society. This study aims to identify and understand how Islamic monetary policy to address inflation affects economic growth. The importance of Islamic currency is not only on demand and supply, but on the principles of justice and brotherhood, which result in equality and fair distribution of wealth. This qualitative research uses literature studies.The literature method consists of a series of actions related to library data collection techniques. This action includes searching for and collecting various books, journals, and scientific works that contain the ideas studied to verify these ideas and draw conclusions. Fiscal policy, monetary policy and other political instruments can be applied to address inflation in the perspective of Islamic economics.